2008
DOI: 10.1161/hypertensionaha.107.107078
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Exercise Training Delays Heart Failure and Improves Survival in Female Hypertensive Heart Failure Rats

Abstract: Abstract-Exercise training improves functional capacity and quality of life in patients with heart failure. However, the long-term effects of exercise on mortality associated with hypertensive heart disease have not been well defined. In the present study, we investigated the effect of low-intensity exercise training on disease progression and survival in female spontaneously hypertensive heart failure rats. Animals with severe hypertension (16 months old) were treadmill trained (14.5 m/min, 45 min/d, 3 d/wk) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 56 publications
2
62
2
1
Order By: Relevance
“…us one of the major bene�ts of exercise training in hypertension is the preservation of cardiomyocyte cell number. Despite the potential for exercise training to increase myocardial mass in pressure overload, most studies have reported an improved phenotype aer training [25,30,46,61,[80][81][82][83][84][85][86][87]. One of the most proli�c bene�ts of exercise training is its improvement on adrenergic signaling.…”
Section: Cardiac Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…us one of the major bene�ts of exercise training in hypertension is the preservation of cardiomyocyte cell number. Despite the potential for exercise training to increase myocardial mass in pressure overload, most studies have reported an improved phenotype aer training [25,30,46,61,[80][81][82][83][84][85][86][87]. One of the most proli�c bene�ts of exercise training is its improvement on adrenergic signaling.…”
Section: Cardiac Remodelingmentioning
confidence: 99%
“…Beyond improved AR responsiveness with training in hypertension, exercise has generally been shown to improve the overall heart phenotype and prolong survival [86,87]. While extreme levels of acute and chronic exercise may be deleterious to the heart by increasing apoptosis, �brosis, and ischemic dysfunction [62,113,114], moderate levels of exercise seem protective from cardiac damage.…”
Section: -Adrenergic Responsivenessmentioning
confidence: 99%
“…Short axis M-mode echocardiograms on the LV were obtained for measurement of LV internal diameters at diastole (LVIDd) and systole (LVIDs), fractional shortening (FS), ejection fraction (EF), anterior wall thickness in diastole (AWTd), and posterior wall thickness in diastole (PWTd) as previously described ( 43 ).…”
Section: Echocardiographic Analysismentioning
confidence: 99%
“…While the control mechanisms for the induction of cardiomyocyte proliferation remain unclear, one theory purports the involvement of a resident population of cardiac progenitor cells (1, 30), which have been shown to increase their activity in stress-induced pathological conditions (1,28,31). In the hypertensive heart, cardiomyocyte proliferation may counteract apoptosis, thus reducing the progressive loss of cardiomyocytes.Recent studies from our laboratory, as well as others, have shown an overall phenotypical improvement for the myocardium with exercise training in hypertension (3,17,24,34,35,42). However, the precise putative mechanisms associated with the observed adaptations with exercise training remain unclear.…”
mentioning
confidence: 92%